Engaging employees through effective performance management: an empirical examination. Issue 5 (24th April 2020) - Kakkar, Shiva; Dash, Sanket; Vohra, Neharika; Saha, Surajit
Abstract : Purpose: Performance management systems (PMS) are integral to an organization's human resource management but research is ambivalent on their positive impact and the mechanism through which they influence employee behavior. This study fills this gap by positing work engagement as a mediator in the relationship between perceptions of PMS effectiveness, employee job satisfaction and turnover intentions. Design/methodology/approach: The study uses a survey-based design. Data were collected from 322 employees in India attending a management development program at a premier business school. Partial least squares–based structure equation modeling package ADANCO was used for data analysis. Findings: Positive perception of PMS effectiveness was found to enhance employee work engagement. This increased job satisfaction and reduced turnover intentions among employees. Thus, work engagement mediated the relationship between PMS perceptions and job satisfaction and turnover intentions. Practical implications: The results suggest that organizations need to focus on three characteristics of PMS, namely its distinctiveness, consistency and consensus. These characteristics determine the effectiveness of PMS in engaging employees and influencing their job satisfaction and turnover intentions. Originality/value: Prior studies on performance management have largely been limited to aspects of justice and focused disproportionately on the appraisal aspect of performance management. This study takes a systems view of performance management and addresses prior shortcomings by examining the role of clarity and horizontal fit between PMS practices in determining employee engagement. The study also provides much needed empirical support to theoretical studies which have argued that PMS is a driver of engagement in organizations (Gruman and Saks, 2011; Mone and London, 2014).